Legal Protection for Police Doctors in Assignments Under Police Operational Control (BKO) Based on Law Number 17 of 2023 Concerning Health (Case Study of Papua Cartenz Peace Operation) - Satria Yuniar Santoso, Stefanus; Arpangi, Arpangi (UNISSULA Semarang, 2025)
Abstract. Police Medicine as a suporting function deploys police doctor personnel in BKO activities to carry out their duties always attached to other police personnel in the field to provide technical assistance in organizing health for police members, as the main and foremost spearhead starting from establishing health post facilities, and preparing medicines and basic medical equipment in maintaining health, preventing disease, improving health, treating disease and restoring the health of police members during assignments both in disaster operation areas and conflict areas. In carrying out their duties, police doctors also provide health services to local communities, both those who are not affected by disasters and conflicts, so that they have a good level of health. The reasons for the elimination of punishment so as to free doctors from lawsuits, namely: Treatment risk, Medical accident, Contribution negligence, Respectable minority rules & error of (in) judgment, Volenti non fit iniura or assumption of risk, and Res Ipsa Loquitur. The Indonesian Medical Disciplinary Honorary Council (MKDKI) has the authority to examine and make decisions on complaints related to the discipline of doctors and dentists. MKDKI can determine whether or not there are errors made by doctors and dentists in the aplication of medical and dental disciplines. This institution is an autonomous institution of the Indonesian Medical Council which is independent in carrying out its duties. Research sourced from the SOEPRA journal entitled